SISTEM INFORMASI AKUNTANSI BERBASIS MOBILE DALAM PENINGKATAN KINERJA - Sipen Royen; Ahmad Sumarlan; Hesti Setiorini (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
Utilizing a mobile-based accounting information system is wise for improving performance. With a mobile-based accounting information system, a sales report data input system can be created that is automatic, effective and accurate. This research aims to find out how a mobile-based accounting information system improves performance. The data collection methods and techniques used in this research were descriptive qualitative methods and direct interviews with employees managing mobile-based accounting information systems. The data used comes from documentation. The research results show that a mobile-based accounting information system at Alfamart has been implemented. Furthermore, the mobile-based accounting information system has been running well using a computer-based information system with a point of sales (POS) application as a transaction tool and the Alfa Gift application is an application launched by PT Alfamart to make it easier for customers to shop online, so recording can be done directly. in input, with the existence of a mobile-based accounting information system, transaction activities are faster and more accurate so that the level of sales and purchasing interest increases, thereby increasing employee performance. Keywords: Earning Per Share, Mobile Based  Accounting Information System, Performance Improvement